2021
DOI: 10.1017/s0266462321001689
|View full text |Cite
|
Sign up to set email alerts
|

Glycated hemoglobin as a surrogate for evaluating the effectiveness of drugs in diabetes mellitus trials: a systematic review and trial-level meta-analysis

Abstract: Objective The objective of this study was to investigate whether glycated hemoglobin (HbA1c) is a valid surrogate for evaluating the effectiveness of antihyperglycemic drugs in diabetes mellitus (DM) trials. Methods We conducted a systematic review of placebo-controlled randomized clinical trials (RCTs) evaluating the effect of a treatment on HbA1c (mean difference between groups) and clinical outcomes (relative risk of mortality, myocardial infarction, stroke, heart failure, and/or kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…In addition, LogRRs are closer to 0 than LogORs enhancing the similarity of both results. Consistent with the recently published meta-analysis by Rivera et al, we found no convincing evidence for surrogacy of HbA1c in terms of mortality [ 12 ]. The differences in LogRRs and correlation coefficients between the study by Rivera et al (LogRR 0.320 [95% CI − 0.151; 0.791]; Pearson's correlation coefficient 0.328 [− 0.148; 0.681]) and our present analysis (LogRR 0.129 [− 0.043; 0.302]; correlation − 0.010 [− 0.145; 0.134]) might be attributable to methodological differences, differences in the inclusion criteria or publication periods of the trials.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, LogRRs are closer to 0 than LogORs enhancing the similarity of both results. Consistent with the recently published meta-analysis by Rivera et al, we found no convincing evidence for surrogacy of HbA1c in terms of mortality [ 12 ]. The differences in LogRRs and correlation coefficients between the study by Rivera et al (LogRR 0.320 [95% CI − 0.151; 0.791]; Pearson's correlation coefficient 0.328 [− 0.148; 0.681]) and our present analysis (LogRR 0.129 [− 0.043; 0.302]; correlation − 0.010 [− 0.145; 0.134]) might be attributable to methodological differences, differences in the inclusion criteria or publication periods of the trials.…”
Section: Discussionsupporting
confidence: 85%
“…Based on the evidence of numerous randomized trials, we conclude that HbA1c is not a valid surrogate marker for all-cause mortality in people with type 2 diabetes. Our results strengthen the rationale that clinical decisions should not only be guided by glycemic parameters, but should also take into account patient-relevant outcomes [ 12 , 24 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In recent years, with the change of people's lifestyle and environmental deterioration, the incidence of clinical pulmonary heart disease is increasing year by year [ 20 ]. In a variety of visceral heart disease, about 20%~40% are pulmonary heart disease [ 21 24 ]. Pulmonary heart disease is mostly induced by chronic obstructive pulmonary disease, and it is a slow occurrence and development process [ 25 ].…”
Section: Discussionmentioning
confidence: 99%